Case of incomplete fibular hemimelia with tarsal coalition, pes planus, ball and socket ankle - Doğan, Emrah; Gül, Süha; Çullu, Neşat; Mouline Doğan, Marwa (Journal of Surgery and Medicine, 2019)
Fibular hemimelia (FH) is a congenital disease with a clinical spectrum ranging from mild fibular hypoplasia to fibular aplasia. There is no proven genetic factor. Some anomalies can accompany FH such as tarsal coalition, ulnar hemimelia, amelia, syndactyly, several extremity anomalies, renal anomalies and cardiac anomalies. Our case is about unilateral and incomplete type of right-side FH in a 14 years old female patient. Tibia was curved (bowing) and short. Disparity of measure with left lower extremity was monitored. Tarsal coalition in osseous form, tibial curve anomaly and small bone part placed in fibula distal region compatible with FH, were visualized. There was curved joint form in the same ankle with hemimelia compatible with ball and socket ankle deformity. Calcaneal inclination angle was 120. The findings were compatible with pes planus.